2018
DOI: 10.12971/2179-5959/agrotecnologia.v9n2p18-27
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento Da Comunidade Microbiana No Sistema Silviagrícola Na Região De Cerrado

Abstract: O sistema integração lavoura – floresta vem sendo considerado inovador com alto potencial na recuperação de áreas degradadas. Porém seu impacto na qualidade do solo necessita de maiores estudos tornando imprescindível estabelecer indicadores adequados para detecção de mudanças na qualidade do solo. O presente trabalho teve por objetivo apresentar variáveis microbiológicas como indicadoras de qualidade no sistema agroflorestal. O experimento foi realizado na fazenda experimental da Universidade Estadual de Goiá… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(8 reference statements)
1
0
1
Order By: Relevance
“…Our result for CO 2 -C disagree with those of T. E. B. Santos et al (2018), who found a lower value in an agroforestry system (1.52 mg CO 2 -C.kg of Semina: Ciênc. Agrár.…”
Section: Soil Propertiescontrasting
confidence: 99%
See 1 more Smart Citation
“…Our result for CO 2 -C disagree with those of T. E. B. Santos et al (2018), who found a lower value in an agroforestry system (1.52 mg CO 2 -C.kg of Semina: Ciênc. Agrár.…”
Section: Soil Propertiescontrasting
confidence: 99%
“…T. E. B. Santos et al (2018) obtained a value close to ours [5.44 mg CO 2 -C. mg C-MB -1 kg -1 h -1 ).10 3 ], which is considered low. According to Novak et al (2018), the lower the qCO 2 , the more efficient the use of C by microbial biomass, and the lower the C losses in the form of CO 2 .…”
Section: Soil Propertiessupporting
confidence: 65%